2019
DOI: 10.1515/corrrev-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment on the corrosion properties of CuAlMn shape memory alloys

Abstract: This paper reports on the influence of heat treatment on the corrosion properties of CuAlMn alloy in 0.1%, 0.9% and 1.5% NaCl solution (pH = 7.4). Heat treatment of alloy samples was performed by samples annealing at 900°C for 30 min. Electrochemical methods of investigations included measuring the open circuit potential (Eoc) and linear and potentiodynamic polarisation. Optical microscopy, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) were used to study the morphology and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…It is observed that the current density of the step-quenched A 7b are dissimilar to those of A alloys in terms of their polarization behavior. The pseudo-passive zone, which follows the Tafel region of the anodic branches of polarization curves, is where the anodic current densities show a slight decrease due to the formation of soluble corrosion products on the surface of the samples [45]. In corrosion studies of Cu-Al-Mn SMAs by Vrsalović et al, [45] and Cu-Zn-Ni SMAs by [34], similar anodic behavior has been observed.…”
Section: Corrosion Properties Of Cu-zn-sn-based Smasmentioning
confidence: 67%
See 2 more Smart Citations
“…It is observed that the current density of the step-quenched A 7b are dissimilar to those of A alloys in terms of their polarization behavior. The pseudo-passive zone, which follows the Tafel region of the anodic branches of polarization curves, is where the anodic current densities show a slight decrease due to the formation of soluble corrosion products on the surface of the samples [45]. In corrosion studies of Cu-Al-Mn SMAs by Vrsalović et al, [45] and Cu-Zn-Ni SMAs by [34], similar anodic behavior has been observed.…”
Section: Corrosion Properties Of Cu-zn-sn-based Smasmentioning
confidence: 67%
“…The pseudo-passive zone, which follows the Tafel region of the anodic branches of polarization curves, is where the anodic current densities show a slight decrease due to the formation of soluble corrosion products on the surface of the samples [45]. In corrosion studies of Cu-Al-Mn SMAs by Vrsalović et al, [45] and Cu-Zn-Ni SMAs by [34], similar anodic behavior has been observed. There is a marginal difference in corrosion density for the up-quenched (4.18 mA/cm 2 ) and directquenched (3.98 mA/cm 2 ) samples while the step-quenched samples had the least corrosion density (3.04 mA/cm 2 ).…”
Section: Corrosion Properties Of Cu-zn-sn-based Smasmentioning
confidence: 67%
See 1 more Smart Citation
“…Analize EDS i XPS (rendgenska fotoelektronska spektroskopija) pokazale su da se korozivni proizvodi sastoje uglavnom od aluminijevih i manganovih oksida i klorida. 68 Ispitivanje korozijskog ponašanja legure Cu- Korozijsko ponašanje legure Cu-11Al-3,4Mn-3,2Zn u 0,5 mol dm −3 otopini Na 2 SO 4 pri različitim temperaturama elektrolita ispitano je različitim nedestruktivnim elektrokemijskim metodama, kao što su mjerenje potencijala otvorenog strujnog kruga, metoda linearne polarizacije i elektrokemijske impedancijske spektroskopije kao i destruktivnim metodama u širokom području potencijala, kao što su potenciodinamička polarizacijska metoda i metoda cikličke polarizacije. 76 Rezultati ispitivanja pokazali su negativan utjecaj temperature elektrolita na korozijsku otpornost legure, što je vidljivo iz negativnosti vrijednosti E OC , opadanja vrijednosti polarizacijskog otpora, porasta vrijednosti gustoće korozijske struje kao i smanjivanja polumjera kapacitivnog polukruga kod impedancijskih mjerenja (slika 18).…”
Section: Mikrostrukturna I Fraktografska Analizaunclassified
“…Cu-Al-Ni and Cu-Al-Mn SMAs have been extensively investigated and have found practical usage in actuator and sensor manufacturing, electronics, computers parts, automotive and aircraft industries, robotics, and civil engineering industry, etc. [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%